EKSPERIMENTASI PEMBELAJARAN KOOPERATIF TIPE CO-OP-CO-OP TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI MINAT BELAJAR SISWA - Suci Nadia Sari; Ferinaldi; Ade Susanti (Mat-Edukasia, 2021)
This research aims to describe the mathematical communication skills taught by the co-op-co-op cooperative learning model in terms of high, medium, and low learning interests better then conventional learning. This study uses a quantitative approach and an experimental method with a 2x3 factorial design. Data collection techniques in this study used a description test of mathematical communication skills and student learning interest questionnaires. The data in this study were tested using the t-test. From the result of the study were obtained: hypotheses 1 and 3 were obtained mathematical communication skills taught with co-op-co-op type cooperative learning models are beter than convetional learning. hypotheses 2 and 4 were obtained mathematical communication skills taught with co-op-co-op type cooperative learning models are nobetter than convetional learning. Hypotheses 5 there is an interaction between cooperative learning models of co-op-co-op type and conventional learning interest in influencing mathematical communication skills.